Incorporating Risk into Technical Efficiency via a Semiparametric Analysis: The Case of ASEAN Banks - Ngo, Thanh Tra (H. : ĐHQGHN, 2018)
The objective of this paper is to incorporate risk in the technical efficiency of listed ASEAN banks in a panel data framework for the period 2000 to 2015. Many researchers apply frontier estimation techniques such as data envelopment analysis (DEA) or stochastic frontier analysis (SFA) for their efficiency analysis. However, the banks' complex production process requires more sophisticated techniques to account for internal structures within the black box, so relying on only traditional DEA or SFA is not adequate to deal with a multiple-input and multipleoutput production technology. To incorporate undesirable outputs such as risk into inefficiency, we rely on the directional distance function (DDF). We employ the DDF under both a parametric (SFA) and semi-parametric (SEMSFA) framework to make comparison efficiency scores with risk adjusted in two scenarios. Our results suggest that risk is such an important factor that bank managers should pay more attention to achieve long-term efficiency in ASEAN banks.